(untitled) (Journal of International Studies, 2023)
During his administration from 2003 to 2009, Abdullah Ahmad Badawi chose to continue the foreign policy of Mahathir Mohamad. However, he also applied a more ‘middle-ground’ approach that was neither provocative nor aggressive. This had on occasion portrayed him as a weak leader, contributing to the loss of majority seats for Barisan Nasional (BN) in the 12th general election. Nonetheless, during his tenure, there was an increase in cooperation between Malaysia and China in the educational and sociocultural fields, as well as cooperation with government-linked companies (GLCs), which had not happened before. How far did the moderate personality of Abdullah provide a significant impact on the structuring of Malaysia’s foreign policy towards China? This research will look at a three-level analysis that was conducted in assessing the foreign policy of Malaysia towards China during the period. The three levels that were analysed were international, national, and personality factors. A neoclassical realist approach was applied to look at the changing international political landscape and its impact on Malaysian foreign policy towards China. This research applied a qualitative method of obtaining primary data through structured interviews with key informants and an analytical method based on chronology—unsupported by empirical evidence from secondary data. In conclusion, the research revealed that Malaysia’s foreign policy towards China during Abdullah Badawi’s administration was a combination of ongoing maturing of relations and an increase in bilateral cooperation which had not been explored before. The research also found that although Abdullah Badawi was seen as a relatively weak leader in domestic politics, he made a significant impact on the continuity of Malaysia’s national interest, particularly in the soft power competition between the USA and China in Southeast Asia.